2020
DOI: 10.1038/s41598-020-78419-7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of activity of brown adipose tissue in lymphoma patients

Abstract: The determinants of brown adipose tissue (BAT) activity are not yet known in detail but might serve as future therapeutic targets against obesity and the metabolic syndrome. We analyzed 235 datasets of lymphoma patients with two PET/CT examinations at different time points retrospectively. We assessed the anthropometric characteristics, features related to the metabolic syndrome, thyroid dysfunction, season of the PET/CT examination, weight change, prior cancer history, lymphoma subgroups, disease activity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…A direct correlation between BAT volume and mortality was described in a large group of cancer patients ( 55 ). However, two recent studies failed to demonstrate a link between BAT activation and weight loss ( 56 , 57 ). Factors influencing detection of BAT activity using FDG-PET/CT scan were described in a large retrospective study ( 58 ).…”
Section: Adipose Tissue Thermogenesis and Browningmentioning
confidence: 99%
“…A direct correlation between BAT volume and mortality was described in a large group of cancer patients ( 55 ). However, two recent studies failed to demonstrate a link between BAT activation and weight loss ( 56 , 57 ). Factors influencing detection of BAT activity using FDG-PET/CT scan were described in a large retrospective study ( 58 ).…”
Section: Adipose Tissue Thermogenesis and Browningmentioning
confidence: 99%
“…Interestingly, a number of studies have shown the activation of brown/beige adipose tissues in animal models of cancer [ 14 , 164 , 165 , 166 ] and in patients with different types of tumor (such as hepatocellular carcinoma, pancreatic adenocarcinoma, anaplastic carcinoma of the lung, etc.) [ 15 , 167 , 168 , 169 ]. Such thermogenic activation has been suggested to contribute to the increased EE in cancer-associated cachexia, a condition characterized by a remarkable body-weight reduction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its high energy consumption BAT is considered to be an important target to prevent obesity and metabolic disorders [12,13]. This theory is supported by reports that activated BAT significantly increases whole-body energy expenditure by oxidizing substantial amounts of glucose and fats [13].…”
Section: Introductionmentioning
confidence: 93%
“…BAT was initially found in small hibernating mammals, as a thermogenic fat tissue [8]. However, the introduction of fluorine 18 ( 18 F) fluorodeoxyglucose (FDG) positron emission tomography (PET)/computed tomography (CT) in clinical oncology practice and the discovery of very high glucose uptake in the cervical and supraclavicular regions led to the incidental discovery of BAT in adults [3,12,14,20]. The Brown Adipose Reporting Criteria in Imaging STudies (BARCIST) criteria, which were recently introduced for a standardised acquisition and evaluation of PET images in this condition, improve the reproducibility of BAT imaging studies.…”
Section: Introductionmentioning
confidence: 99%